2019
DOI: 10.1111/echo.14370
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms, pathophysiology, and diagnostic imaging of left ventricular outflow tract obstruction following mitral valve surgery and transcatheter mitral valve replacement

Abstract: Left ventricular outflow tract obstruction is a serious complication of mitral valve surgery (repair and replacement) and transcatheter mitral valve replacement. An appreciation of the various mechanisms which cause outflow obstruction in these settings is critical to avoiding this complication and to initiating appropriate treatment. This article discusses the mechanisms, pathophysiology, and imaging of left ventricular outflow tract obstruction which can arise following insertion of a variety of mitral valve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The absence of increased LVOT obstruction risk with mitral bioprosthesis implantation in the left atrium could be attributed to 2 factors: (1) the intra-atrial insertion strategy reduces the entry height of the bioprosthetic valve strut into the LVOT; and (2) the choice of an appropriately oversized prosthesis, unrestricted by the calcified mitral annulus' diameter, enhances the aortic-mitral angle and directs the strut away from the LVOT. 29 …”
Section: Discussionmentioning
confidence: 99%
“…The absence of increased LVOT obstruction risk with mitral bioprosthesis implantation in the left atrium could be attributed to 2 factors: (1) the intra-atrial insertion strategy reduces the entry height of the bioprosthetic valve strut into the LVOT; and (2) the choice of an appropriately oversized prosthesis, unrestricted by the calcified mitral annulus' diameter, enhances the aortic-mitral angle and directs the strut away from the LVOT. 29 …”
Section: Discussionmentioning
confidence: 99%
“…15 Individual patient characteristics that predispose to LVOTO, such as aortomitral angulation, septal thickness, and a small LV cavity, should be assessed. 16 Computed tomography software and computer-based models have been developed to predict the risk of LVOTO following transcatheter mitral valve replacement. 17 These models may be helpful in selecting surgical patients for retention of the AML, in association with further research into the methods by which the AML can be safely preserved.…”
Section: Discussionmentioning
confidence: 99%
“…11 It has also been reported that minor changes in the left ventricular outflow anatomy, including the aorto-septal angle, 9 can produce significant alterations in the dynamic forces and septal shear stress, and thus influencing the development and the progression of sub-aortic obstruction, which is much faster in infants than in older children. 12,13 These mechanical theories, however, could not explain the increased familial recurrence rate that is also well-identified in cases with sub-aortic membranes; an underlying genetic factors must therefore be coexistent. 8,[14][15][16] A theory that combines both the mechanical and the genetic hypothesis states that the disturbed flow dynamics might induce the expression of a number of genes responsible for endothelial and smooth muscle cell proliferation, similar to the mechanisms involved in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%